2018
DOI: 10.1245/s10434-018-6391-z
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes After Distal Pancreatectomy with Celiac Axis Resection for Pancreatic Cancer: A Pan-European Retrospective Cohort Study

Abstract: BackgroundWestern multicenter studies on distal pancreatectomy with celiac axis resection (DP-CAR), also known as the Appleby procedure, for locally advanced pancreatic cancer are lacking. We aimed to study overall survival, morbidity, mortality and the impact of preoperative hepatic artery embolization (PHAE).MethodsRetrospective cohort study within the European-African Hepato-Pancreato-Biliary-Association, on DP-CAR between 1-1-2000 and 6-1-2016. Primary endpoint was overall survival. Secondary endpoints wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 32 publications
4
56
0
Order By: Relevance
“…In a recent retrospective international multicenter study including 191 patients undergoing DP‐CAR, the 90‐day mortality rate was 5.5% at five high‐volume but as high as 18% at 18 low‐volume DP‐CAR centers, demonstrating the importance of experience with this rare and complex procedure . In a multicenter study performed in 20 European centers in 12 countries, the median survival of 68 patients undergoing DP‐CAR was 18 months . A recent single‐center study reported a very favorable median survival of 38.6 months with a strategy of neoadjuvant therapy followed by DP‐CAR in pancreatic cancer with celiac axis involvement, recommending a neoadjuvant strategy in these patients .…”
Section: Surgical Techniques To Increase Local Radicality In Pancreatmentioning
confidence: 99%
“…In a recent retrospective international multicenter study including 191 patients undergoing DP‐CAR, the 90‐day mortality rate was 5.5% at five high‐volume but as high as 18% at 18 low‐volume DP‐CAR centers, demonstrating the importance of experience with this rare and complex procedure . In a multicenter study performed in 20 European centers in 12 countries, the median survival of 68 patients undergoing DP‐CAR was 18 months . A recent single‐center study reported a very favorable median survival of 38.6 months with a strategy of neoadjuvant therapy followed by DP‐CAR in pancreatic cancer with celiac axis involvement, recommending a neoadjuvant strategy in these patients .…”
Section: Surgical Techniques To Increase Local Radicality In Pancreatmentioning
confidence: 99%
“…Historically, in our institution, vascular involvement has not been deemed an absolute contraindication for resection [6,[11][12][13][14].We started with vein resection and, after some experience, we evolved to resect also arterial segments (P-Ar). Initially, arterial resection was considered when technically feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial resections during pancreatectomies were proven to be technically feasible (30)(31)(32)(33), but the rate of postoperative complications including postoperative mortality is high (34,35), with highly controversial oncological benefits for patients with PDAC (33,34). Resection of combined PV/ SMV resection with superior mesenteric artery resection during pancreatectomies for PDAC were associated with up to 91% morbidity rates and 20% mortality rates, as a recent systematic review has shown (34).…”
Section: Discussionmentioning
confidence: 99%